2012
DOI: 10.1111/j.1745-9125.2012.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Violent Victimization and Precocious Union Formation*

Abstract: This article bridges scholarship in criminology and family sociology by extending arguments about “precocious exits” from adolescence to consider early union formation as a salient outcome of violent victimization for youths. Research indicates that early union formation is associated with several negative outcomes; yet the absence of attention to union formation as a consequence of violent victimization is noteworthy. We address this gap by drawing on life course theory and data from the National Longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 77 publications
1
35
2
Order By: Relevance
“…In cases where data were available for both parents, we selected the higher combined score. Numerous studies have adopted this approach using Add Health (Haynie, Doogan, and Soller 2014; Haynie, Steffensmeier, and Bell 2007; Kuhl, Warner, and Wilczak 2012; Roettger et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…In cases where data were available for both parents, we selected the higher combined score. Numerous studies have adopted this approach using Add Health (Haynie, Doogan, and Soller 2014; Haynie, Steffensmeier, and Bell 2007; Kuhl, Warner, and Wilczak 2012; Roettger et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…In cases where data were available for both parents, we selected the higher combined score. 3 Numerous studies have adopted this approach using Add Health (Haynie, Doogan, and Soller 2014; Haynie, Steffensmeier, and Bell 2007; Kuhl, Warner, and Wilczak 2012; Roettger et al 2011). …”
Section: Life Course Transitions Ses and Delinquencymentioning
confidence: 99%
“…However, despite the links between YVV and other precocious exits, few scholars have assessed whether (and how) YVV might influence the formation and quality of young adult romantic or intimate unions. One exception is a study by Kuhl, Warner, and Wilczak (), which found that victims of youth violence experienced subsequently higher rates of first coresidential union formation, especially marriage, in the transition to adulthood. That is, victims entered into coresidential unions earlier than their nonvictimized peers; however, the consequences of this earlier union timing among victims of youth violence remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Youth violent victimization (YVV) increases the risk of subsequent victimization (Lauritsen and Davis Quinet, ) and is associated with role transitions that mark a precocious exit from adolescence and premature entry into adulthood (Hagan and Foster, ; Haynie et al., ). Such precocious role exits have largely been considered hallmarks of continued disadvantage (e.g., high‐school dropout, teen pregnancy, and running away); yet a recent study by Kuhl, Warner, and Wilczak () found that YVV also leads to early intimate union formation. Whether such early unions are indicative of continued disadvantage remains unclear.…”
mentioning
confidence: 99%